Análisis Multitemporal de Cambio en el Espejo de Agua del Río Cusiana Mediante Procesamiento Digital de Imágenes Landsat (2021)
In this degree work, the change in the water surface of the Cusiana river was identified for an area of interest selected in the vicinity of the municipalities of Aguazul, Tauramena and Maní in the department of Casanare, based on the availability of information. and other selection criteria. For this, the digital processing was realized by analyzing of five satellite images of the Landsamission, it was taken in January between 1986 and 2021. It was carried out in order to observe, extract and measure the area occupied by the water surface, finally the displacement was identified to the area of interest for subsequent multitemporal analysis. An increase in the water surface was highlighted in 2021 compared to 1986. It was consistent with the “average daily flow” (IDEAM, n.d.) registered during January 2021. However, the displacement of the water surface of the Cusiana river was interesting about it meant both the loss of the bank, or surrounding coverage, of the riverbed, as well as the recovery of 32.1 hectares of vegetation cover at the end of the study period.